PERLINDUNGAN HUKUM TERHADAP HAK PEREMPUAN SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA (KAJIAN PERSPEKTIF HAK ASASI MANUSIA) - Margie Gladies Sopacua (SASI, 2016)
Issues of justice and human rights in relation to the enforcement of the law is not a simple job to be realized. Violence against women in general is a serious problem experienced by many women in Indonesia, because this issue is like a small pyramid on top but large at the bottom because it's hard to get an exact figure because of the "sensitivity" of the issue. Violence against women is all forms of violence resulting in pain or suffering to women including threats,hamper, curb, negating the enjoyment and constitutes a violation of Human Rights, whichresulted in suffering the physical, psychological, or sexual well occurs outside or within thescope of the household itself.